2018
DOI: 10.1371/journal.pone.0193884
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neuroprotective efficacy of poly-arginine R18 and R18D (D-enantiomer) peptides following permanent middle cerebral artery occlusion in the Wistar rat and in vitro toxicity studies

Abstract: We have previously demonstrated that arginine-rich and poly-arginine peptides possess potent neuroprotective properties, with poly-arginine peptide R18 identified as being highly effective at reducing infarct volume following middle cerebral artery occlusion (MCAO) in the Sprague Dawley rat. Since peptides synthesised using D-isoform amino acids have greater stability than L-isoform peptides due to increased resistance to proteolytic degradation, they represent potentially more effective peptide therapeutics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
4
22
0
Order By: Relevance
“…The present study adds to our previous findings which demonstrate the neuroprotective effectiveness of R18 and R18D in a P7 rat model of perinatal HIE (Edwards et al, ), and other acute neuronal injury models (Chiu et al, ; Edwards et al, ; Meloni et al, ; Meloni, Brookes, et al, ; Meloni, Milani, et al, ; Milani et al, ; Milani, Clark, et al, ; Milani, Cross, et al, ; Milani, Knuckey, et al, ). Importantly, the present study examined the neuroprotective efficacy of R18D when administered 30, 60 or 120 min after HI.…”
Section: Discussionsupporting
confidence: 77%
“…The present study adds to our previous findings which demonstrate the neuroprotective effectiveness of R18 and R18D in a P7 rat model of perinatal HIE (Edwards et al, ), and other acute neuronal injury models (Chiu et al, ; Edwards et al, ; Meloni et al, ; Meloni, Brookes, et al, ; Meloni, Milani, et al, ; Milani et al, ; Milani, Clark, et al, ; Milani, Cross, et al, ; Milani, Knuckey, et al, ). Importantly, the present study examined the neuroprotective efficacy of R18D when administered 30, 60 or 120 min after HI.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, the ability of R18 treatment to attenuate excitotoxicityinduced protein changes underlying loss of mitochondrial integrity, provides evidence that the peptide helps preserve the function of the organelle in times of cellular stress. In line with the ability of CARPs to maintain mitochondrial function and energy generation, in this and previous studies R18 was demonstrated to increase MTS metabolism in uninjured neurons and in neurons after exposure to glutamic acid [14].…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies in our laboratory have identified cationic arginine-rich peptides (CARPs), which include poly-arginine peptides, as a novel class of neuroprotective agents. In particular, we have demonstrated that poly-arginine-18 (R18, 18-mer of arginine) is neuroprotective in in vitro neuronal excitotoxicity models and in vivo in rodent models of stroke [11][12][13][14][15][16][17][18], hypoxic-ischaemic encephalopathy (HIE) [19], and traumatic brain injury (TBI) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with in vitro findings, CARPs (e.g., R9D, R12, R18, R18D, protamine; Tables 1, 3) were also demonstrated to provide significant neuroprotection and improve functional outcomes in rat models of permanent and/or transient middle cerebral artery occlusion (MCAO), perinatal hypoxia-ischemia and traumatic brain injury (15,16,(18)(19)(20)(21)(22)(23)(24)212) and a non-human primate MCAO stroke model (26). Positive neuroprotective effects with R9D and R18D, which are the D-enantiomers of R9 and R18, also confirmed the lack of stereo-specificity for CARP efficacy in vivo.…”
Section: Further Validation and Characterization Of Carps As Neuroprosupporting
confidence: 70%